Dimensioning Field-Grading Materials in Cable Joints by Adjoint Transient Finite-Element Sensitivity Analysis - Ruppert, Maren Greta; De Gersem, Herbert; Späck-Leigsnering, Yvonne; Koch, Myriam (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
An adjoint sensitivity analysis of a nonlinear transient finite-element model allows to determine the sensitivities of the key performance indicators of a cable joint with respect to the parameters of an embedded field-grading material. The example considers a high-voltage DC cable joint submitted to an overvoltage event.